Chemoenzymatic Syntheses of Sialylated Oligosaccharides Containing C5‐Modified Neuraminic Acids for Dual Inhibition of Hemagglutinins and Neuraminidases. Issue 30 (18th June 2015) - Birikaki, Lémonia; Pradeau, Stéphanie; Armand, Sylvie; Priem, Bernard; Márquez‐Domínguez, Luis; Reyes‐Leyva, Julio; Santos‐López, Gerardo; Samain, Eric; Driguez, Hugues; Fort, Sébastien
Abstract A fast chemoenzymatic synthesis of sialylated oligosaccharides containing C5‐modified neuraminic acids is reported. Analogues of GM3 and GM2 ganglioside saccharidic portions where the acetyl group of NeuNAc has been replaced by a phenylacetyl (PhAc) or a propanoyl (Prop) moiety have been efficiently prepared with metabolically engineered E. coli bacteria. GM3 analogues were either obtained by chemoselective modification of biosynthetic N‐acetyl‐sialyllactoside (GM3NAc) or by direct bacterial synthesis using C5‐modified neuraminic acid precursors. The latter strategy proved to be very versatile as it led to an efficient synthesis of GM2 analogues. These glycomimetics were assessed against hemagglutinins and sialidases. In particular, the GM3NPhAc displayed a binding affinity for Maackia amurensis agglutinin (MAA) similar to that of GM3NAc, while being resistant to hydrolysis by Vibrio cholerae (VC) neuraminidase. A preliminary study with influenza viruses also confirmed a selective inhibition of N1 neuraminidase by GM3NPhAc, suggesting potential developments for the detection of flu viruses and for fighting them.